Magnetic field effects on the rest potential of ferromagnetic electrodes - COEY, JOHN MICHAEL DAVID (IEEE, 2002)
The application of a magnetic field unexpectedly alters the rest potential of ferromagnetic electrodes in paramagnetic solutions of their salts. Anodic shifts of up to 60 mV in a field of 1 tesla were observed for 1Miron electrodes in iron nitrate solution. The magnitude of the shift depends on magnetic field strength and orientation and it varies with the anion used. The shift is smaller for cobalt and nickel ( 2 mV) than for iron. The effect is attributed to modifications in the rate of mass transport under the influence of the magnetic field gradient force.
PUBLISHED
Keywords: Electrode, ferromagnetic, field gradient force, magnetic field, magnetoelectrochemistry, rest potential.